Effect of Different Wrap Films on Physico-Chemical Properties of Tray Packaged Boneless Chicken Chunks Stored at -18±2 °C - Kumar Banerjee, Dipak; Prince Devadason, Immanuel; Ahmad, Tanbir; Talukder, Suman; Ratan Sen , Arup (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The need for the proper and convenient packaging methods of meat like tray packaging is surging in India. This study was designed to evaluate influence of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high density polyethylene (HDPE) and polyvinylchloride (PVC) wrap films on various physico-chemical properties (pH, instrumental colour, water activity, TBARS, tyrosine value and extract release volume) of boneless chicken at frozen (-18±2 °C) conditions. About 200 g of deboned chicken was aerobically packed separately in food grade polypropylene trays, heat sealed and studied at 1 month interval for 3 months. In frozen storage deboned chicken had good qualities in the case of all the treatment films for a period of 3 months. Tray packaged chicken sealed with HDPE film had better qualities and chicken sealed with PVC film had better colour (L, a,b) characteristics than that of other films. Thus, it can be concluded that tray packaging of meat sealed with HDPE film can be successfully used under frozen conditions for maintenance of better quality.